Reproducibility of quantitative indices of lung function and microstructure from 129Xe chemical shift saturation recovery (CSSR) MR spectroscopy. Issue 6 (1st July 2016) - Stewart, Neil J.; Horn, Felix C.; Norquay, Graham; Collier, Guilhem J.; Yates, Denise P.; Lawson, Rod; Marshall, Helen; Wild, Jim M.
Abstract : Purpose: To evaluate the reproducibility of indices of lung microstructure and function derived from 129 Xe chemical shift saturation recovery (CSSR) spectroscopy in healthy volunteers and patients with chronic obstructive pulmonary disease (COPD), and to study the sensitivity of CSSR‐derived parameters to pulse sequence design and lung inflation level. Methods: Preliminary data were collected from five volunteers on three occasions, using two implementations of the CSSR sequence. Separately, three volunteers each underwent CSSR at three different lung inflation levels. After analysis of these preliminary data, five COPD patients were scanned on three separate days, and nine age‐matched volunteers were scanned three times on one day, to assess reproducibility. Results: CSSR‐derived alveolar septal thickness (ST) and surface‐area‐to‐volume (S/V) ratio values decreased with lung inflation level ( P  < 0.001; P  = 0.057, respectively). Intra‐subject standard deviations of ST were lower than the previously measured differences between volunteers and subjects with interstitial lung disease. The mean coefficient of variation (CV) values of ST were 3.9 ± 1.9% and 6.0 ± 4.5% in volunteers and COPD patients, respectively, similar to CV values for whole‐lung carbon monoxide diffusing capacity. The mean CV of S/V in volunteers and patients was 14.1 ± 8.0% and 18.0 ± 19.3%, respectively. Conclusion: 129 Xe CSSR presents a reproducible method for estimation of alveolar septal thickness. Magn Reson Med 77:2107–2113, 2017. © 2016 The Authors Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.